(untitled) (International Journal of Educational Management, Rivers State University., 2025)
The study investigated implementation strategies of National Policy on Inclusive education as perceived administrators in secondary schools in Port-Harcourt Metropolis in Rivers State. Two specific objectives, research questions and two hypotheses guided the study. The study adopted descriptive survey design. The population of the study was 759 school administrators comprising of 718 school administrators in government approved private secondary schools and 41 school principals in public secondary schools in Port Harcourt Metropolis. The sample size of the study was 328 school administrators comprising 287 private school administrators and 41 public school administrators derived through simple random sampling and census techniques. The instrument for data collection was a self-structured questionnaire titled: “Implementation Strategies of Inclusive Education as Perceived by Administrators in Secondary Schools Questionnaire”. The instrument was subjected to face and content validity by experts in Department of Educational Management and Measurement and Evaluation. The reliability of the instrument was established using Cronbach Alpha Method which yielded reliability coefficients of 0.70 and 0.81. Mean and standard deviation were used to answer the research questions while z-test was used to test the hypotheses at 0.05 level of significance. The study found that to high extent accessibility and safety and support for inclusive teaching enhance the implementation of inclusive education as perceived by administrators in Port-Harcourt Metropolis, Rivers State. Based on the findings, the study recommended among others that government and school proprietors should make accessibility and safety means available in all schools to accommodate variety of disabilities as this will help create an inclusive learning environment for gifted students, disabled students and others.